KERAGAMAN GULMA DI PERTANAMAN PADI AROMATIK METODE SRI PADA LAHAN SAWAH TADAH HUJAN YANG DIAPLIKASI PUPUK NPK DAN KOMPOS JERAMI PADI - Anshary, Muhammad Saifuddin; Saputra, Riza Adrianoor; Santoso, Untung; Jumar, Jumar (Jurnal Agroteknologi, 2025)
Rainfed rice fields are wetlands whose use is still not optimal, so proper management is needed so that they can be utilized for rice cultivation. In efforts to improve land productivity, the concept of a sustainable rice cropping system has been developed which takes into account environmental conditions known as the System of Rice Intensification (SRI). One of the serious limiting factors in the utilization of rainfed lowland rice fields is the problem of weeds. This study aims to determine the diversity of weeds in rainfed paddy fields planted with aromatic rice and fertilized with NPK fertilizer combined with rice straw compost. This study used a 2-factor randomized block design (RBD). The first factor was the dose of NPK fertilizer (A), namely: a0 = 0 kg ha-1 (control), a1 = 150 kg ha-1, and a2 = 300 kg ha-1, and the second factor is the dose of rice straw compost (K), namely: k1 = 5 t ha-1, k2 = 7.5 t ha-1, k3 = 10 t ha-1, k4 = 12.5 t ha-1, k5 = 15 t ha-1, and k6 = 20 t ha-1. The results showed that there were six types of weeds found in the aromatic rice planting area in rainfed lowland rice fields that were applied with NPK fertilizer and rice straw compost, namely Cyperus rotundus, Chloris radiata, Cyperus iria, Echinochloa colona, Ludwigia palustris, and Amaranthus spinosus. The weed that dominated rainfed lowland rice planted with aromatic rice with the application of NPK fertilizer and rice straw compost was Cyperus rotundus, with a summed dominance ratio (SDR) of 58–100% found in the a2k6 treatment (300 kg ha-1 NPK + 20 t ha-1 rice straw compost). The highest weed diversity index (H') value was found in the a0k1 treatment (0 kg ha-1 + 5 t ha-1 rice straw compost) at a 45 DAP of 1.10.